2007
DOI: 10.1103/physrevb.76.054408
|View full text |Cite
|
Sign up to set email alerts
|

Frustration effects in antiferromagnets on planar random graphs

Abstract: We consider the effect of geometric frustration induced by the random distribution of loop lengths in the "fat" graphs of the dynamical triangulations model on coupled antiferromagnets. While the influence of such connectivity disorder is rather mild for ferromagnets in that an ordered phase persists and only the properties of the phase transition are substantially changed in some cases, any finite-temperature transition is wiped out due to frustration for some of the antiferromagnetic models. A wealth of diff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 54 publications
3
16
0
Order By: Relevance
“…Also, we reach much larger system sizes than previous work ͑also a bit larger than the recent study in Ref. 18, which is anyway for a different lattice type͒, which also reduces systematic errors due to unknown corrections to scaling. For the ±J model it was found that the MEDW energy saturates at a nonzero value for large system sizes, 7,23 which means = 0.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Also, we reach much larger system sizes than previous work ͑also a bit larger than the recent study in Ref. 18, which is anyway for a different lattice type͒, which also reduces systematic errors due to unknown corrections to scaling. For the ±J model it was found that the MEDW energy saturates at a nonzero value for large system sizes, 7,23 which means = 0.…”
Section: Introductionmentioning
confidence: 77%
“…24͒ and d f = 1.283͑11͒. 18 Nevertheless, in these works there is still no systematics concerning the selection of a representative 27,28 suggested that the behavior of zero-energy DWs is not consistent with the droplet scaling picture. In this context it was proposed to treat MEDWs of zero and non zero energies as distinct classes.…”
Section: Introductionmentioning
confidence: 97%
“…Such consistence together with further assumptions would suggest a relation between stiffness exponent and fractal dimension, d f = 1 + 3/[4(3 + θ)]. 38 For the bimodal model, on the other hand, the fractal dimension is possibly different [41][42][43] , but calculations are complicated by sampling problems since the ground-state algorithms do not produce the degenerate ground states with the correct weights. These subtle differences between results for different coupling distributions and excitation types call for high-precision studies to distinguish random from systematic coincidences.…”
Section: Introductionmentioning
confidence: 99%
“…In the meantime, there have been many studies of Boolean variables on scale-free networks [2][3][4][5] and, more recently, even with competing interactions [6][7][8][9][10]. There is general consensus that stable ferromagnetic and spin-glass phases emerge in these complex systems [10] and that for particular choices of the decay exponent λ the critical temperature diverges, i.e., Boolean variables with competing interactions are extremely robust to local perturbations.…”
Section: Introductionmentioning
confidence: 99%